Population‐based study of the impact of surgical and adjuvant therapy at the same or a different institution on survival of patients with pancreatic adenocarcinoma. Issue 1 (5th December 2018) - Latchana, N.; Davis, L.; Coburn, N. G.; Mahar, A.; Liu, Y.; Hammad, A.; Kagedan, D.; Elmi, M.; Siddiqui, M.; Earle, C. C.; Hallet, J.
Abstract : Background: Pancreatic cancer surgery is increasingly regionalized in high‐volume centres. Provision of adjuvant chemotherapy in the same institution can place a burden on patients, whereas receiving adjuvant chemotherapy at a different institution closer to home may create disparities in care. This study compared long‐term outcomes of patients with pancreatic adenocarcinoma receiving adjuvant chemotherapy at the institution where they had undergone surgery with outcomes for those receiving chemotherapy at a different institution. Methods: This was a population‐based study of patients receiving adjuvant chemotherapy after resection of pancreatic adenocarcinoma performed at ten designated hepatopancreatobiliary centres in Ontario, Canada, between 2004 and 2014. Patients were divided into those receiving chemotherapy at the same institution as surgery or a different institution from where surgery was performed. The primary outcome was overall survival (OS). Multivariable Cox regression assessed the association between OS and each chemotherapy group, adjusted for potential confounders. Results: Of 589 patients, 374( 63·5 per cent) received adjuvant chemotherapy at the same institution as surgery. After adjusting for age, sex, co‐morbidity, socioeconomic status, rural living, tumour stage, margin positivity and year of surgery, the location of adjuvant chemotherapy was not independently associated with OS (hazard ratio 1·03, 95 per cent c.i. 0·85 to 1·24). For patients who underwent chemotherapy at a different institution, mean travel distance to receive chemotherapy was less (22·9 km) than that needed for surgery (106·7 km). Conclusion: After pancreatectomy for pancreatic adenocarcinoma at specialized hepatopancreatobiliary surgery centres, OS was not affected by the location of the centre delivering adjuvant chemotherapy. Receiving this treatment in a local centre reduced patients' travel burden. Abstract : In this population‐based analysis including 589 patients, overall survival was not impacted by the location of provision of adjuvant chemotherapy, whether at the same institution where surgery had been performed or a different institution (hazard ratio 1·03, 95 per cent c.i. 0·85 to 1·24). However, receipt of adjuvant chemotherapy at a different institution than a specialized surgery centre allowed for shorter travel times for patients. Adjuvant therapy can be delivered safely close to home